Some ancestral heritage, geomorphology in Peru and its contribution to the tasks of land use planning - Durand Castro, David Mansueto (2015)
In Peru, the occurrence of catastrophic events causes irreparable loss of human lives and extensive material damage. These effects are increasing in scope and intensity in recent years, just as the demands increase at almost all scientific disciplines linked to land preparation tasks, demanding proposals for preventive actions or mitigation. This requirement gets extended particularly to geomorphology. In Peru, the standpoint linked to the positions aligned with the idealist, generalizing and deductivist lines of the classic Davisian geomorphology approach, is being now gradually replaced by the development of a systemic, morphoclimatic and inclusive approach. The result is that starting from direct observation of the land; this approach has contributed to the solution of concrete problems. This article discusses some experiences in the use, management and land occupation by our ancient culture, related to the most relevant landforms and modeling processes. In general, many of these manifestations of the use, management and land use, have been lost in time and only some of the most powerful remain over the obsession to eradicate them from discrimination and the lack of interest of many, or the preference of many others to imported models applied as templates; today you can see that an important part of these imported models not only have not yielded the expected results, but have also obscured the inherited territory gained, exposing it to underestimation and discrimination. Emphasis is given on those practices and forms of physical occupation of territory by ancient pre-Inca and Inca cultures which, introduced into the natural environment, have been clear signs of sustainability